2022
DOI: 10.3389/fimmu.2022.914010
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Lactococcus lactis Expressing Grass Carp Reovirus VP6 Induces Mucosal Immunity Against Grass Carp Reovirus Infection

Abstract: Grass carp haemorrhagic disease caused by grass carp reovirus II is a serious disease of the aquaculture industry and vaccination is the only effective method of GCRV protection. In this study, Lactococcus lactis was used as oral vaccine delivery to express the GCRV II VP6 protein. We evaluated the protective efficacy of the live vaccine strain to induce mucosal immune protection. After oral administration, the recombinant strains remained in the hindgut for antigen presentation and increased the survival rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Compared with inactivated vaccine and live‐attenuated vaccine, the recombinant subunit vaccine and DNA vaccine could effectively present antigen epitope and safely stimulate cellular and humoral immune response 176 . For recombinant subunit vaccines, the protective antigen epitopes of GCRV proteins are expressed in different expression systems such as E. coli , Bacillus subtilis , Lactococcus lactis , Saccharomyces cerevisiae and Baculovirus in vitro using recombinant DNA technology 177–181 . Research has reported that the recombinant fibre protein VP56, outer capsid proteins such as VP35 and VP7, and the inner capsid proteins such as VP3, VP4 and VP6 can effectively elicit a protective immune response against GCRV infection 49,180,182–184 .…”
Section: The Strategies To Suppress Aqrvs Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with inactivated vaccine and live‐attenuated vaccine, the recombinant subunit vaccine and DNA vaccine could effectively present antigen epitope and safely stimulate cellular and humoral immune response 176 . For recombinant subunit vaccines, the protective antigen epitopes of GCRV proteins are expressed in different expression systems such as E. coli , Bacillus subtilis , Lactococcus lactis , Saccharomyces cerevisiae and Baculovirus in vitro using recombinant DNA technology 177–181 . Research has reported that the recombinant fibre protein VP56, outer capsid proteins such as VP35 and VP7, and the inner capsid proteins such as VP3, VP4 and VP6 can effectively elicit a protective immune response against GCRV infection 49,180,182–184 .…”
Section: The Strategies To Suppress Aqrvs Infectionmentioning
confidence: 99%
“…176 For recombinant subunit vaccines, the protective antigen epitopes of GCRV proteins are expressed in different expression systems such as E. coli, Bacillus subtilis, Lactococcus lactis, Saccharomyces cerevisiae and Baculovirus in vitro using recombinant DNA technology. [177][178][179][180][181] Research has reported that the recombinant fibre protein VP56, outer capsid proteins such as VP35 and VP7, and the inner capsid proteins such as VP3, VP4 and VP6 can effectively elicit a protective immune response against GCRV infection. 49,180,[182][183][184] Interestingly, the VP4 gene of GCRV-II is divided into 4 segments and used for screening for potential antigen epitope.…”
Section: Different Types Of Vaccines Used To Against Gcrv Infectionmentioning
confidence: 99%